2022
DOI: 10.1002/mabi.202100407
|View full text |Cite
|
Sign up to set email alerts
|

Silk Fibroin Crosslinked Glycyrrhizic Acid and Silver Hydrogels for Accelerated Bacteria‐Infected Wound Healing

Abstract: Antibacterial hydrogels are intensively studied as wound dressings. Silk fibroin (SF) is chemical crosslinked to glycyrrhizic acid (GA) and silver to fabricate a hydrogel dressing with both antibacterial and anti-inflammatory properties. The SF/Ag/GA hydrogel exhibits high water content with acceptable mechanical properties, combines the good biocompatibility and biodegradability of SF, the antibacterial activity of silver, and the anti-inflammatory property of GA, capable to promote tissue regeneration during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Silk fibroin (SF) is a natural protein-based biopolymer [ 54 , 60 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ]. Silk fibers are primarily composed of proteins derived from silkworms, namely fibroin, sericin, and 18 different amino acids [ 56 , 113 ].…”
Section: Polymersmentioning
confidence: 99%
“…Silk fibroin (SF) is a natural protein-based biopolymer [ 54 , 60 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 ]. Silk fibers are primarily composed of proteins derived from silkworms, namely fibroin, sericin, and 18 different amino acids [ 56 , 113 ].…”
Section: Polymersmentioning
confidence: 99%
“…101 Furthermore, silver nanoparticles with antibacterial properties and glycyrrhizic acid (GA) with anti-inflammatory properties were also introduced into the silk fibroin hydrogel matrix to generate a dressing for wound healing. 102 structure of which contributes to the strength and hierarchical structure of bone tissue. 103 Benefiting from their high toughness, robust mechanical strength, excellent biocompatibility, and slow biodegradability, silk fibroin hydrogel-derived bone tissue engineering scaffolds have been developed as a very popular choice.…”
Section: Skin Regenerationmentioning
confidence: 99%
“…The structural amphiphilicity and chirality make GA molecules display anisotropic self-assembly behavior in aqueous solutions, forming long and semiflexible nanofibrils with a right-handed twist, 2.5 nm thickness, and 9 nm periodicity, which further form supramolecular hydrogels with a hydrogen-bond 3D network at a concentration over 0.3 wt %. , Our previous studies have shown that the controllable assembly of these GA nanofibrils at liquid interfaces and in the aqueous phase makes them highly suitable as building blocks for preparing multiphase colloidal materials with high stability, stimulability, and processability. Furthermore, the multiple functional groups, rigid skeletons, and unique stacking behaviors of GA molecules render them as an ideal platform for creating various GA derivatives, which can be further used as building blocks to develop versatile soft material. , Inspired by the unique combination of the interesting self-assembly and the inherent biological activities, we speculate that GA can be used as natural bifunctional building blocks for fabricating bioactive hydrogels with the capability to combat bacterial infections, suppress inflammatory responses, and thereby restore wound tissue function back to normal physiological activity. Recent studies also demonstrate that GA-based bioactive hydrogels show the potential for wound dressings. However, owing to the lack of adequate mechanical strength, adhesion, and self-healing ability, the GA hydrogel dressings would be easily damaged by normal human body movement or local stress, which results in low therapeutic efficiency and limits their practical biomedical applications. Therefore, endowing the GA hydrogels with sufficient mechanical strength and multifunctionality is critical for the development of new bioactive GA hydrogel dressings with ideal potential clinical transformation effects.…”
Section: Introductionmentioning
confidence: 99%